On Adaptive Estimation of Bacterial Growth in the Competitive Chemostat. Issue 16 (2019) - de Souza, Alex dos Reis; Gouzé, Jean-Luc; Polyakov, Andrey; Efimov, Denis
Abstract: In this paper, the problem of state estimation of a bioreactor containing a single substrate and several competing species is studied. This scenario is well-known as a competition model, in which multiple species compete for the same nutrient. The goal is to estimate concentrations of the substrate and all species, considering the concentration of total biomass as measurement. To address such a challenge, the estimation scheme relies in the coupling of two estimation techniques: an asymptotic observer, which takes advantage of the model structure being independent of its kinetics, and a finite-time parameter estimation technique, which also drops the usual requirement of persistence of excitation.